Menanggapi hadist maudhu’ di era digital - Jannah, Richatul (Maliki Interdisciplinary Journal, 2025)
Hadith is the second primary source of Islamic teachings after the Qur’an and plays a vital role in guiding Muslims in daily life. However, the emergence of fabricated hadiths maudhu’ poses a serious threat to the authenticity of Islamic teachings, especially in the digital age. Through social media, false hadiths can spread rapidly without proper verification, potentially misleading the public, creating division, and harming interreligious harmony. This article explores the historical background of fabricated hadiths, the driving factors behind their creation, and the efforts made by scholars to combat them, including isnad and matn criticism. It also emphasizes the responsibility of every Muslim to verify religious information, especially that which circulates online. Solutions such as religious education, digital literacy, and a critical approach to hadith are key to preventing misinformation. This study aims to raise public awareness about the dangers of fabricated hadiths and promote collective efforts to preserve the authenticity of the Prophet’s legacy in an age of overwhelming information